Evaluation of the Egyptian Local Strains of Chickens - Kosba, M.A.; Abd El-Halim (2008)
The present study aimed to evaluate some local chicken breed in Egypt. The result indicated that the average of fertility %, hatchability %, body weight at 4 and 8 weeks of age for males, females and combined sexes as well as age at sexual maturity, egg number and egg mass during the first 90 days of laying for these breeds were: 90.16%, 77.68%, 229.5g, 202.9, 225.5g, 528.7g, 582.5g, 1628.2g, 170.8 days, 45.5eggs and 1459g.